Biomarkers to discriminate between aseptic loosened and stable total hip or knee arthroplasties: a systematic review - Shaho Hasan; Peter van Schie; Bart L Kaptein; Jan W Schoones; Perla J Marang-van de Mheen; Rob G H H Nelissen (EFORT Open Reviews, 2024)
Aseptic loosening is the leading cause for revision of total hip and total knee arthroplasties (THAs/TKAs) reported in national arthroplasty registries (1, 2). Aseptic loosening may have a multitude of causes including factors related to implant design, surgical technique, and genetic predisposition (3, 4, 5, 6, 7, 8, 9). For the implant-related causes, polymer, bone cement, and metal wear particles released due to repetitive motion of the joint can induce inflammation and osteolysis (10, 11, 12). The latter may differ between individuals due to reaction of the foreign body inflammatory response (4, 13). Other mechanisms influencing aseptic loosening such as stress shielding, micromotion, high fluid pressure, and endotoxins have been proposed as well (14, 15, 16, 17).